US foreign policy decision-making from kennedy to obama : responses to international challenges - Hybel, Alex Roberto; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2014)
This book analyzes the foreign policy decision-making processes of Presidents John F. Kennedy, Lyndon B. Johnson, Richard Nixon, George H.W. Bush, George W. Bush, and Barack Obama during military intervention by way of contemporary foreign policy decision-making models (FPDMs).
Keywords: Political science; United States -- History; World politics; Europe -- Politics and government; International relations; Political Science and International Relations; European Politics; Political History; Political Science; US History; Foreign Policy